2005
DOI: 10.1021/bi051367p
|View full text |Cite
|
Sign up to set email alerts
|

On the Mechanism of Activation of the BLUF Domain of AppA

Abstract: AppA, a transcriptional antirepressor, regulates the steady expression of photosynthesis genes in Rhodobacter sphaeroides in response to high-intensity blue light and to redox signals. Its blue-light sensing is mediated by an N-terminal BLUF domain, a member of a novel flavin fold. The photocycle of this domain (AppA(5-125)) includes formation of a slightly red-shifted long-lived signaling state, which is formed directly from the singlet excited state of the flavin on a subnanosecond time scale [Gauden et al. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
138
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 99 publications
(148 citation statements)
references
References 50 publications
10
138
0
Order By: Relevance
“…3D). These observations are consistent with previous results on AppA, which showed no H͞D exchange effect on the excited-state lifetimes (20). FAD* has an isosbestic point at 610 nm, giving a clean view on the kinetic behavior of the intermediate species.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…3D). These observations are consistent with previous results on AppA, which showed no H͞D exchange effect on the excited-state lifetimes (20). FAD* has an isosbestic point at 610 nm, giving a clean view on the kinetic behavior of the intermediate species.…”
Section: Resultssupporting
confidence: 93%
“…In this way, the FAD •Ϫ and FADH • intermediates do not transiently accumulate during the reaction and therefore escape detection. A rate-limiting light-driven ET rather than a hydrogen transfer in the AppA BLUF domain is consistent with the absence of a KIE on the FAD excited-state lifetime upon H͞D exchange (20). …”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…This observation is quite remarkable given that in the AppA BLUF domain the corresponding mutation leads to acceleration of the photocycle (37). The S28A mutant has a dark recovery of 4 s, essentially the same as in WT.…”
Section: Resultsmentioning
confidence: 77%
“…In the AppA BLUF domain it was shown that the semiconserved tryptophan in the vicinity of FAD (W104) also contributes to electron transfer to the flavin (20,37). The latter observation lended support to the "W-in" conformation of W104 in darkstate AppA.…”
mentioning
confidence: 89%